Carbon Intensity, Renewable Energy Consumption and SDG8 – Decent Work and Economic Growth in MINT Countries - Zhang, Weiwei; Zhang, Erfu (Problemy Ekorozwoju, 2026)
This study investigates the interplay between carbon intensity, renewable energy consumption, and SDG 8—Decent Work and Economic Growth in the MINT countries (Mexico, Indonesia, Nigeria, and Turkey) over 2000–2023, encompassing pre-, during-, and post-COVID-19 periods. Employing a multi-method empirical strategy, the analysis combines Panel Autoregressive Distributed Lag (PARDL) within the Pooled Mean Group framework, country-level Fixed Effects (FE) estimation, and Method-of-Moments Quantile Regression (MM-QR) to capture short- and long-run dynamics, country-specific heterogeneity, and distributional effects. Results reveal marked heterogeneity across countries and periods. Long-run PARDL estimates indicate that GDP per capita and carbon intensity are primary drivers of SDG 8, while energy use and renewable energy exert nuanced effects. COVID-19 interactions highlight that both carbon-intensive and renewable sectors temporarily stabilised employment and growth. FE and MM-QR results show Mexico and Turkey benefited from positive linkages between renewable energy adoption and SDG 8, whereas Indonesia and Nigeria faced weaker or negative associations, reflecting structural and policy constraints. Quantile analyses further demonstrate that lower-performing economies are more vulnerable to the adverse effects of carbon-intensive activities and less able to translate renewable energy investments into decent work gains. Structural break tests confirm the pandemic as a regime-shifting event, altering the impact of growth, energy use, and carbon intensity on SDG 8. This study contributes to the literature by integrating dynamic, country-specific, and distributional perspectives on the energy–growth–employment nexus, providing actionable insights for policies that promote inclusive, low-carbon, and resilient economic development in MINT economies.